STRATEGI MARKETING BANK MEGA SYARIAH KCP PALEMBANG BASUKI RAHMAT DALAM MENINGKATKAN PRODUK PEMBIAYAAN BERBASIS BANK DIGITAL - Ulil Amri (CV. Cendekiawan Muda Sriwijaya, 2024)
In everyday life, people cannot be separated from real transactions or digital transactions. In the past few years, the digital banking trend is considered to be experiencing quite rapid development. One of the factors in the development of this digital bank comes from a practical and fast process. Because of this, Mega Syariah Bank KCP Palembang Basuki Rahmat provides customer service through digital bank-based financing and continues to apply an Islamic economic perspective with the aim of retaining customers. This research aims to determine the influence of digital banks on customer decisions and community satisfaction from an Islamic economic perspective. This research uses a qualitative method. The data source that the researcher used was primary data sources obtained from 1 person in the marketing field, as well as 20 people and secondary data sources obtained from books, journals and theses related to the research object. Data collection methods, researchers used interview and documentation methods. Based on the research results, they used strategies, namely marketing strategies through open tables, door to door, word of mouth, social media. And to make it easier to achieve targets, research was carried out using the application of segmentation, targeting and positioning. And also implement a marketing mix that becomes one unit in order to increase customers in digital bank-based financing.